1997
DOI: 10.1590/s0100-879x1997000500003
|View full text |Cite
|
Sign up to set email alerts
|

Connexin domains relevant to the chemical gating of gap junction channels

Abstract: Most cells exchange ions and small metabolites via gap junction channels. These channels are made of two hemichannels (connexons), each formed by the radial arrangement of six connexin (Cx) proteins. Connexins span the bilayer four times (M1-M4) and have both aminoand carboxy-termini (NT, CT) at the cytoplasmic side of the membrane, forming two extracellular loops (E1, E2) and one inner (IL) loop. The channels are regulated by gates that close with cytosolic acidification (e.g., CO 2 treatment) or increased ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…The possible role of CaM in the chemical gating of the β -family Cxs was first proposed by Peracchia and Wang [51]. CaM co-localizes with Cx32 [9] and directly gates Cx32-containing gap junctions [52].…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of CaM in the chemical gating of the β -family Cxs was first proposed by Peracchia and Wang [51]. CaM co-localizes with Cx32 [9] and directly gates Cx32-containing gap junctions [52].…”
Section: Discussionmentioning
confidence: 99%
“…Since essential regulatory domains for the opening and closing of gap junction channels are located at the COOH terminus of connexins [7,11,23,25], it was not surprising that these channels were defective in coupling. It was unexpected, however, that this defect in regulatory competence of a connexon is no longer detectable when a trCx45 connexon is paired with an intact connexon.…”
Section: Discussionmentioning
confidence: 99%
“…The permeability of these channels can be regulated by different mechanisms, such as changes in transjunctional voltage [1,29,31] or intracellular pH [11], but phosphorylation [20] and the binding of ligands [30] may also affect their conductance. The regulatory sites for these gating processes are presumably located at the COOH end [25] of the channel-forming protein, the connexin (Cx). A hexamer of these proteins forms one hemichannel, the connexon, which can pair with an identical connexon of a neighbouring cell, thus establishing a permeable homotypic cell-cell channel.…”
Section: Introductionmentioning
confidence: 99%
“…They initially postulated differential roles for the 1 st and 2 nd segments of the intracellular loop (CL 1 and CL 2 ) in V j -gating and CO 2 -induced (pH) gating, respectively. As deletion of most of the CT of Cx32 did not affect its CO 2 -sensitivity, but replacement of the arginines at the beginning of the CT (dubbed CT 1 ) with asparagines greatly increased CO 2 -gating, Peracchia and Wang [152] suggested that interaction occurs between negative residues in CL 1 with positive residues either in CT 1 or CL 2 , with the open channel resulting from CL 1 -CT 1 interaction and the chemically (pH, Ca) gated closed channel resulting from CL 1 -CL 2 interaction. Evidence that positive charges at CT 1 were key to the CO 2 -sensitivity, but not V j -sensitivity was presented [216] and incorporated into a model in which CT 1 acts as “a latch that keeps the channel open by immobilizing the CL, a potential gating element.” Breaking the CL 1 -CT 1 interaction would be part of the gating process that enables the CL (not CT) to move toward the channel pore and close the channel.…”
Section: Gating Elementsmentioning
confidence: 99%